CAPABILITIES OF INDIGENOUS FISH SWIMMING WITH NUMBER OF DIFFERENT GROUPS IN RURAL TENGKAN CHANNELS - Dessy Kristina; Nofrizal Nofrizal; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTDessykristina65@gmail.com Knowledge about fish behavior is highly needed in developing effective fishing techniques and methods. One of the fish behaviors that can be learned for fishing gear is fish swimming activity. Fish swimming activities can be divided into three large groups, namely suistained, prolonged, and swimming speed. This study uses an experimental method / observation that is the speed and endurance of fish swimming tested on a flume tank with different current speeds in each group of tilapia and this research was carried out in March 2019 at the Fishing Equipment Laboratory, Department of Resource Utilization of the Faculty of Fisheries and Ocean University of Riau. The purpose of this study is to determine and test the endurance of tilapia swimming from various types of fish at different current speeds and to determine the swimming speed and maximum swimming speed.swimming speed maximum sustained of 5 tailed tilapia is 2,2 BL / sec,swimming speed maximum sustained of 10 tailed tilapia is 2,3 BL / sec, andswimming speed maximum sustained of 15 tailed tilapia is 2,0 BL / seconds. Thespeed prolonged of the 5-tailed tilapia group is 2.2 - 8.2 BL / sec, thespeed prolonged of the 10-tailed tilapia group is 2.3–8.0 BL / sec, and thespeed prolonged of the 15-tailed tilapia group is in the range of 2.0 -7.7 BL / sec. These results indicate that at this speed it is good to use active fishing gear to catch tilapia in waters. After knowing the speed of swimming, this tilapia can make an efficient fishing gear in fishing so that it increases fishing yields for fishermen. Keywords: Fish swimming speed, Tilapia swimming endurance, Water current